INVESTIGATION OF WITHDRAWAL RESISTANCE OF LAG SCREWS FROM BANGKIRAY WOODS - Sudarsana, I Ketut (Jurnal Ilmiah Teknik Sipil; Vol. 9, No. 1 Januari 2005)
Lag screws are commonly used in knock down constructions where screws is not possible. The resistance of the lag screws is provided by friction between threaded parts and wood. This paper presents experimental investigation of withdrawal strength of lag screws embedded into Bangkiray woods. The objectives of the investigation were to determine the behavior of embedded screws subjected to withdrawal forces. To meet the experimental objectives, three specimens of an 8 mm diameter lag screw embedded into a 80 x 150 x 600 mm bangkiray woods were assembled and tested to failure. The lag screws were 100 mm long with threaded length of 60 mm (effective length of 55 mm). However, in this experiment, only 40 mm of the threaded part was penetrated into the main wood and giving the effective penetration length of 35 mm. Direction of the screw was perpendicular to wood grains. Two equal point loads were applied on both sides of the screws through two pieces of 50 x 70 x 500 mm bangkiray woods connected using screws. The loads were increased incrementally every 1 kN or 1kN/minute. Axial deformations of the screws were measured using a dial gauge located at the center of the lag screws for every load increment. The results show that failure modes occurred due to failure of the woods which were bearing failure of side beams and pull-out of the screws due to lose of main beam resistence. These types of failure were mainly dictated by the absence of washers between the bearing wood and the head of the screws. Slip of the embedded part at maximum load is about 9.25% and 10.93% of the embedded length. The average maximum withdrawal strength of the screw embedded 40 mm into bangkiray wood is 12.0 kN, excluding data of specimen S1. Prediction of withdrawal strength for embedment length of 60 mm is 24.10 kN.
Keywords: withdrawal test, lag screws, connections, fasteners, bankiray wood